An investigation to understand the contribution of collagen characteristics to Asian consumers’ eating preference of six different beef shank cuts - Wu, Wanjun (Kansas State University, 2020)
The objective of this study was to evaluate factors affecting Asian consumers’ visual and eating preferences as well as understanding the effect of mature collagen crosslink densities on cooked beef tenderness and connective tissue texture of six different beef shank cuts. Six beef shank muscles, three from the forequarter [biceps brachii (BB); deep digital flexor - foreshank (DDF-F); extensor carpi radialis (ECR)], and three from the hindquarter [flexor digitorum superficialis (FDS), deep digital flexor - hindshank (DDF-H); a combination of long digital extensor, medial digital extensor and peroneus tertius (LMP)] were collected from 12 USDA Low Choice beef carcasses. Shanks from the left sides were designated for cooked treatment (stewed in water for 90 minutes at 93°C) and used for Asian consumer panels, Warner-Bratzler shear force (WBSF) and cooked collagen content and characteristics. The right sides were designated for raw treatment and used for visual panels, objective color measurement, proximate analysis and raw collagen content and characteristics. In addition, soluble and insoluble collagen percentages were calculated. For Asian consumer panels, BB, FDS, and LMP all received higher ratings for tenderness, juiciness, and sensory overall liking, followed by ECR and DDF-H, with DDF-F received the lowest score (P < 0.01). For portion size preference and visual overall liking, BB and ECR received the highest rating, followed by DDF-H, DDF-F and LMP, with FDS received the lowest rating (P < 0.01). For connective tissue characteristics and mature collagen crosslink densities, DDF-F had the toughest connective tissue texture, greatest shear force value, most cooked collagen content, greatest insoluble collagen percentage as well as greatest raw and cooked pyridinoline (PYD) densities among all the beef shank cuts (P < 0.05). It was interesting to note that DDF-F, FDS, and LMP all started with similar raw collagen content (P > 0.10), but DDF-F ended with greater cooked collagen content than the others. Cooking only decreased PYD density for DDF-F (P < 0.05), and PYD density for the rest of the beef shank cuts was not affected by cooking (P > 0.05). Furthermore, a correlation analysis was conducted in order to understand the contribution of collagen characteristics to cooked beef tenderness. Cooked collagen content, insoluble collagen percentage as well as raw PYD densities had positive correlations with connective tissue texture (r = 0.550, 0.498 and 0.560 respectively; P < 0.01) and WBSF (r = 0.615, 0.392 and 0.730, respectively; P < 0.05). This study showed that tenderness and juiciness directly affected Asian consumers’ eating preference, while shank size affected their visual preference for beef shank cuts. Moreover, our results demonstrated that cooked (insoluble) collagen contributed to the background toughness, and PYD is a heat stable collagen crosslink that may require extensive heat treatment to degrade and allow for the solubilization of collagen. In addition, raw PYD density may be a great indicator for cooked beef connective tissue texture and ultimately, tenderness in beef cuts with high concentration of connective tissue prepared with moist heat cookery.
Keywords: Beef shank; Moist heat cookery; Connective tissue; Collagen; Collagen crosslink; Pyridinoline